COSEISMIC DEFORMATION OF THE 2020 BENGKULU MW 6.8 EARTHQUAKE USING INSAR DATA - Ongky Anggara; Satrio Muhammad Alif (GeoEco, 2025)
An earthquake with a seismic moment magnitude of Mw 6.8 occurred in Bengkulu province, located on the southwestern coast of Sumatra, on August 18, 2020. This study aims to assess the application of the differential interferometric synthetic aperture radar (DInSAR) method to detect and analyze coseismic deformation due to this earthquake using the Sentinel-1A radar satellite. The results of the DInSAR did not yield significant coseismic signals with the range of Line of Sight (LOS) displacement of ~-40 mm to ~40 mm. The InSAR data did not detect clear deformation patterns or displacements associated with the August 18, 2020 earthquake. Further investigations are needed to understand the limitations of InSAR in detecting coseismic signals for this specific event. Integrating these datasets can provide a more comprehensive understanding of the earthquake source, fault characteristics, and associated deformation patterns.